Kesiapsiagaan Warga dalam Menghadapi Bencana Banjir di Desa Kleco Kulon Kabupaten Sragen - Devi Gustina Adi Priyanti; Dyah Rahmawatie Ratna Budi Utami (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Floods were natural disaster that happened during the rainy season. According to data in 2019, flood occurrence in Central Java was 102 times. The flood disasters in the Sidoharjo sub-district had been caused by heavy rainfall and the geographical location traversed by two rivers, namely the Bengawan Solo river and the Mungkung river. The purpose of this study was to describe the characteristics of residents in Kleco Kulon Village and to determine the relationship between individual characteristics of residents based on gender, age, and education level with the preparedness of residents in facing flood disasters in Kleco Kulon Village.. This study used quantitative research method with a cross-sectional approach. The sampling technique used was accidental sampling, with the research sample of 70 respondents. Based on sex, the majority of respondents were females, covering up to 65.7%. Based on age, the majority of respondents were late adults with the age range of 36-45 years, covering up to 72.9%. Based on education level, the majority of respondents were high school graduates, covering up to 47.1%. The level of preparedness of residents in Kleco Kulon Village against flood disasters is in the very high category, which is 48.6%. There was a correlation between individual characteristics based on sex, age, and educational level with the flood preparedness of residents in the Kleco Kulon village, with a p value of 0,000 <0.05.